In the ghettos : teens who survived the ghettos of the Holocaust - Ayer, Eleanor H. (New York : Rosen Pub. Group, 1999)
Chronicles the deportation of Jews into ghettos during Hitler's Third Reich and presents the narratives of three individuals who, as teenagers, lived in the ghettos of Lodz, Theresienstadt, and Warsaw and survived physical deprivations, abuse, and deportation to the death camps.
Includes bibliographical references (p. 60-61) and index.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Holocaust, Jewish (1939-1945) -- Personal narratives -- Juvenile literature; Jewish children in the Holocaust -- Juvenile literature; Holocaust, Jewish (1939-1945) -- Personal narratives; Jews -- Biography; Holocaust, 1939-1945 -- Personal narratives; Jewish children -- Biography